Determinants of producer resiliency: investigating the probability that agricultural producers exit the industry in the face of drought - Nelson, Ron, author; Goemans, Christopher, advisor; Pritchett, James, advisor; Shields, Martin, committee member (Colorado State University. Libraries, 2013)
For the last two years agricultural producers in Colorado have been faced with severe drought conditions resulting in significant economic losses. With a changing climate, likely leading to an increased probability of extreme and recurring droughts, it is becoming an ever more important policy concern to determine the effect that drought has on the resiliency of farmers and ranchers. To date, research on farmer resiliency in the developed countries has primarily been theoretical; the majority of empirical work focused on producers in developing countries. This paper analyzes survey data collected from 2012 to investigate which factors impact farmer and rancher drought resiliency within Colorado. Specifically, we are interested in determining if, and how, continued drought impacts the likelihood that farmers and ranchers will leave the industry. Results highlight the relative importance that a producer's overall wealth and the region where their enterprise operates.
Keywords: resilience; agriculture; exit; drought